Single-step conversion of cephalosporin-C to 7-aminocephalosporanic acid by free and immobilized cells of Pseudomonas diminuta - Nigam V.K.; Kundu S.; Ghosh P. (My University, 2025)
7-Aminocephalosporanic acid (7-ACA), the starting material for the production of a number of clinically used semisynthetic cephalosporins, is produced by deacylation of cephalosporin-C. The production of 7-ACA was studied in various modes, at the optimal conditions using free and immobilized whole cells of Pseudomonas diminuta. Copyright © 2005 by Humana Press Inc. All rights of any nature whatsoever reserved.